DETERMINANTS OF OUTSOURCED EMPLOYEE PERFORMANCE: THE ROLES OF SUPERVISORY LEADERSHIP STYLE, WORK DISCIPLINE, AND WORK MOTIVATION - Ananda Oktaviani; Rizky Octavianda; Agung Priyono; Anandha Budiantoro (Journal of Management and Leadership, 2026)
This study aims to examine the influence of supervisory leadership style, work discipline, and work motivation on the performance of outsourced employees at PT Pertamina Retail South Tangerang Area. A descriptive quantitative approach with a survey method was employed. Data were collected through Likert-scale questionnaires distributed to 34 outsourced employees selected using simple random sampling. Data analysis was conducted using SPSS, including validity and reliability tests, classical assumption tests, and multiple linear regression analysis. Hypothesis testing was performed using t-tests, F-tests, and the coefficient of determination (R²). The findings reveal that supervisory leadership style, work discipline, and work motivation partially and simultaneously exert a positive and significant effect on employee performance. Work discipline emerged as the most dominant variable, with a Beta coefficient of 0.657. The R² value of 0.898 indicates that the three independent variables explain 89.8% of the variance in employee performance. These findings highlight the importance of effective leadership practices, consistent work discipline, and enhanced employee motivation in improving workforce performance and service quality within the increasingly competitive energy retail industry.